Gerda's Character as the Influence of Lili's Transition in The Danish Girl Film - Septi Herlinda (Vivid: Journal of Language and Literature, 2022)
This research aims to show how Gerda Wegener, as a supporting character in The Danish Girl film could give the biggest contribution into the main character’s  transition  from  Einar  Wegener  (male)  to  Lili  Elbe  (female) through  Gerda’s  character  and  personality  depicted  in  the  film.  This research uses descriptive qualitative method. To support the analysis, the writer uses the theory of the Big Five personality factors, characterization, and altruism. The result of this research shows that Gerda’s character and personality  are  found  to  be  the  main  cause  of  the  conflict  that  occurred in  the  film,  on  how  the  main  character,  Einar  Wegener  in  overcoming his gender dyphoria to fully transformed into a woman named Lili Elbe. This research discovered that, based on the Big Five personality factors; Gerda’s  personality  in  agreeableness  and  openness  are  highly  relatable in influencing Lili’s transition. Moreover, Gerda’s behavior in altruism is also found to be the main reason on why she chose to support the main character’s gender transition despite the huge loss upon her. In conclusion, Gerda Wegener as a supporting character played the biggest role in stirring the plot by her influence in supporting Einar Wegener’s gender transition. It  also  shows  that  it  is  possible  for  someone  to  be  so  selfless  when  it comes to the person they adore. Finally, it gives a new perspective on how significant the role of a supporting characters are in a film based on their character and personality.